The Influence Factors Interest in Buying on E-commerce - Nuruni Ika Kusuma Wardani; Ignathia Martha Hendrati; Sishadiyati Sishadiyati (Journal of Economics, Business, and Government Challenges, 2020)
Technology in Indonesia is currently experiencing rapid advances in information technology and communication, especially internet advancements. In Indonesia alone, people who use the Internet have increased very rapidly. With the large number of people using the internet in Indonesia, there is a trend of online shopping through websites or online shop applications. Based on these thoughts, it is interesting to examine whether the perception of ease of transaction and trust affect buying interest in e-commerce. The population in this study are consumers who use e-commerce. While the samples taken were 60 respondents. The analysis technique used is Partial Least Square (PLS). From this research it can be seen that the perception of ease of transaction and trust can contribute to e-commerce buying interest.